Analyzing Perceived Risk and E-WOM Influence on Healthy Food Choices Among Generation Z in Malang City, Indonesia - Bawana, Surya Praja Dwi; Maulidah, Silvana; Isaskar, Riyanti; Laili, Fitrotul (Agro Bali : Agricultural Journal, 2025)
The pandemic has shifted societal behavior towards a healthier lifestyle, with 7 out of 10 people in Indonesia desiring healthy food. Malang City, as one of the cities in East Java with many universities, has a significant Gen-Z population influencing the economic activities in the healthy food sector. This study explores the relationship between Perceived Risk and Purchase Decisions and the moderating role of Electronic Word of Mouth (E-WOM) among students in Malang City. Using quantitative methods and SEM-PLS analysis with 100 101 students from Universitas Brawijaya as respondents gathered through questionnaires, this study found that Perceived Risk significantly affects healthy food purchase decisions, and E-WOM is a significant moderating variable in this relationship. The study provides strategic recommendations for marketing and policies related to healthy food, including financial risk control through regular product price evaluations, the creation of social trends to reduce negative stigma among Gen-Z, improved production and delivery efficiency to speed up product reception, and maximizing the role of E-WOM through promoting positive reviews and educational content on social media to build a positive image and increase consumer loyalty.